Evaluation of the piloting of push pull technology in controlling striga and stemborerin maize and sorghum areas of semi-arid northern Ethiopia. Issue 7 (November 2015) - Araya, Hailu; Gereziher, Kifle; Abera, Dejene; Mariam, Haileselassie Ghebre; Reda, Fasil; Gebremeskel, Kidu; Edwards, Sue; Legesse, Hailu; Mohammed, Endris; Asmelash, Arefayne; Misgina, Sara
No abstract available